THE COMPETENCE OF THE FIFTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF FKIP UKI TORAJA IN IDENTIFYING VALUES IN THE FILM “THE THEORY OF EVERYTHING BY JANE WILLIAM” - matius tandi kombong (Teaching English as a Foreign Language Overseas Journal, 2016)
The Objective of this Research is to know the Competence of the Fifth Semester Studentsof English Department of FKIP UKI Toraja in Analyzing Values in The Film “TheTheory of Everything by Jane William”.The population of this research is the Fifth Semester Students of English Department’. Itconsists of nine classes and the number of students is 307. The researcher used Randomsampling technique, because the population is enough large, so the writer choose class Bwith 27 students randomly. The data obtained from the written test, where consist ofmultiple choice, the data is analyzed by used quantitative descriptive method. It was usedto know the students competence in analyzing film “ The Theory of Everything by JaneWilliam”.The result of the research shows that the competence of the fifth semester students inanalyzing film stage in 51. The writer thinks that they happened because most of thestudents still have problem in analyzing value in film “ The Theory of Everything by JaneWilliam”. Based on the result of the research, the writer concludes the studentscompetence in identifying values in the film “The Theory of Everything by Jane Williamstill poor.